Sosialisasi Model Budidaya Udang Vaname Dengan Teknologi “Ecogreen Aquaculture” Bagi Petambak Udang Di Wilayah Kecamatan Mayangan Kota Probolinggo - Febriyani Eka Supriatin; Muhammad Musa; Sri Andayani; Yenny Risjani; Maftuch Maftuch; Asus Maizar Suryanto Hertika Maizar Suryanto Hertika Hertika (Journal of Innovation and Applied Technology, 2022)
The coastal area of Mayangan District is the center of the economic development of the city of Probolinggo. Mangrove forest management that lacks environmental standards such as fish and shrimp ponds and mangroves that are within the scope of the area, causes damage and decreases the quality and sustainability of coastal and marine resources. This Community Service intends to introduce intensive shrimp farming techniques in ponds that are environmentally friendly and sustainable as well as introduce the importance of mangrove ecosystems in coastal areas and in supporting the development of fish/shrimp cultivation business activities by socializing the vannamei shrimp cultivation model with "Ecogreen Aquaculture" technology. The forms of service activities that will be carried out include socializing the vannamei shrimp cultivation model , socializing the importance of mangrove ecosystems in improving the environment in supporting the development of aquaculture activities and trial activities of "Ecogreen Aquaculture" technology.